Customer‐facing supply chain practices—The impact of demand and distribution management on supply chain success - Rexhausen, Daniel; Pibernik, Richard; Kaiser, Gernot (Journal of Operations Management, 2012)
Traditionally, distribution has been viewed as the key (physical) link between a company's internal supply chain activities and its customers. More recently, demand management has emerged as a new dimension at the customer interface. Although it has become increasing popular in industry, it has not yet been analyzed in depth with respect to its impact on supply chain performance. Both distribution management and demand management entail customer‐facing processes and practices and that are interrelated and (may) jointly determine supply chain performance. In this paper we seek to extend the stream of research in supply chain management by systematically investigating the impact of customer‐facing supply chain practices on supply chain performance. Specifically, the paper examines the relative impact of relevant practices associated with demand and distribution management. To this end, we collected data from 116 multi‐national companies based in Europe and analyzed it using structural equation modeling techniques. Our results suggest that (i) high demand management performance has a substantial positive impact on the overall supply chain performance, (ii) this effect is stronger than that of distribution management performance, and (iii) there is no evidence that demand management might be an enabler for effective distribution management. Among the individual practices that constitute demand and distribution management, adherence to the demand and distribution management processes and demand segmentation emerged as the strongest performance levers. Based upon additional in‐depth interviews conducted with selected companies from our sample, we shed light on some of the most important findings that emerged from our survey analysis.